The Market for Mergers and the Boundaries of the Firm - RHODES‐KROPF, MATTHEW; ROBINSON, DAVID T. (Journal of Finance, 2008)
ABSTRACT We relate the property rights theory of the firm to empirical regularities in the market for mergers and acquisitions. We first show that high market‐to‐book acquirers typically do not purchase low market‐to‐book targets. Instead, mergers pair together firms with similar ratios. We then build a continuous‐time model of investment and merger activity combining search, scarcity, and asset complementarity to explain this like buys like result. We test the model by relating like‐buys‐like to search frictions. Search frictions and assortative matching vary inversely, supporting the model over standard explanations.